MicroRNA‐205 affects mouse granulosa cell apoptosis and estradiol synthesis by targeting CREB1. Issue 5 (16th December 2018) - Zhang, Pengju; Wang, Jun; Lang, Hongyan; Wang, Weixia; Liu, Xiaohui; Liu, Haiyan; Tan, Chengcheng; Li, Xintao; Zhao, Yumin; Wu, Xinghong
Abstract: MicroRNA‐205 (miR‐205) is involved in various physiological and pathological processes, but its biological function in follicular atresia remains unclear. In this study, we investigated miR‐205 expression in mouse granulosa cells (mGCs) and analyzed its functions in primary mGCs by performing a series of in vitro experiments. Quantitative real‐time polymerase chain reaction showed that miR‐205 expression was significantly higher in early atretic follicles and progressively atretic follicles than in healthy follicles. miR‐205 overexpression in mGCs significantly promoted apoptosis and caspase‐3/9 activities, as well as inhibited estrogen (E2) release and cytochrome P450 family 19 subfamily A polypeptide 1 (CYP19A1, a key gene in E2 production) expression. Bioinformatics and luciferase reporter assays revealed that the gene encoding cyclic AMP response element (CRE)‐binding protein 1 (CREB1) was a direct target of miR‐205 in mGCs. CREB1 upregulation partially rescued the effects of miR‐205 on apoptosis, caspase‐3/9 activities, E2 production, and CYP19A1 expression on mGCs. These results indicate that miR‐205 might play an important role in ovarian follicular development and provide new insights into follicular atresia Abstract : In summary, the current study revealed that microRNA‐205 (miR‐205) affects ovarian granulosa cell (GC) apoptosis and steroid synthesis, at least to a certain extent by inhibiting cyclic AMP response element (CRE)‐binding protein 1 (CREB1). These findings provide an improved understanding of the molecular mechanisms underlying the regulation of ovarian follicular atresia by miR‐205, suggesting that miR‐205 is a potential target for follicular atresia.